1987
DOI: 10.7567/jjaps.26s1.9
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Two-Dimensional Blood Flow Imaging Using Ultrasound Doppler

Abstract: A newly developed two-dimensional blood flow imaging system which uses ultrasound is described, in which blood flow in a given cross section of a live organ is displayed in real time. To perform this, an autocorrelation technique is used. Obtained blood flow data are displayed in color on a TV screen superimposed on black/white tissue images. The flow direction, speed and variance are expressed by differences in color and brightness. Experiments were conducted with a mechanical and an electrical scanner and go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The flow velocity v may be written in terms of the Doppler shift frequency f d [2] cos 2 c d f cf v (2) where f c is the transducer central frequency, c the velocity of sound in tissue and the angle between the ultrasound beam and the direction of flow motion. Using the well-established autocorrelation method, the Doppler shift frequency f d at depth n is given by…”
Section: Color Flow Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…The flow velocity v may be written in terms of the Doppler shift frequency f d [2] cos 2 c d f cf v (2) where f c is the transducer central frequency, c the velocity of sound in tissue and the angle between the ultrasound beam and the direction of flow motion. Using the well-established autocorrelation method, the Doppler shift frequency f d at depth n is given by…”
Section: Color Flow Imagingmentioning
confidence: 99%
“…The complex operation, such as arctangent (i.e., atan2) is needed to calculate the phase shift of the autocorrelation derived from Doppler signals [2], and in Section 2. To implement the atan2, one can use lookup table (LUT) to save two arguments of atan2 with a compromise between the size of the table and the accuracy of the derived atan2.…”
Section: Introductionmentioning
confidence: 99%
“…It can mathematically be shown that the autocorrelation function contains a number proportional to target movement velocity which can be automatically detected and displayed [4]. The limitations for color flow mapping are very similar to those affecting currently used pulsed Doppler instruments.…”
Section: Introductionmentioning
confidence: 94%